Bearing Run-To-Failure Data Simulation for Condition Based Maintenance - Xinghui Zhang (Institute of Advanced Engineering and Science, 2014)
This paper presents a bearing run-to-failure data simulation model for condition based maintenance, in which a single point outrace fault can be implemented. According to the characteristic that bearing life follows the Weibull distribution, amount of bearing run-to-failure datasets can be simulated which can be used to verify the feature extraction, remaining useful life prediction and maintenance decision methods particularly the methods which use Proportional hazard model. A case study simulating 6205-2RS JEM SKF bearing run-to-failure data is done detailed. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3607